2022
DOI: 10.1111/jocn.16292
|View full text |Cite
|
Sign up to set email alerts
|

Path model on decision‐making ability of clinical nurses

Abstract: Aims and objectives: To identify and examine the relationship between the factors influencing the decision-making ability of clinical nurses in hospitals, South Korea, and to establish a model, to verify the fit and the effect.Background: Clinical nurses are exposed to environments and situations where they make continuous decisions according to the need of direct treatment and nursing.Design: This study used a cross-sectional descriptive design, relation prediction modelling and adheres to the STROBE guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Additionally, the overlay visualization mapping indicated that University of Massachusetts and Kyune Hee University have also made contribution in this field in the recent years (Ayotte et al, 2022;S. M. Kim et al, 2022;Park et al, 2022;Yang et al, 2021). However, the result indicated that no institution in China ranked high regarding publication, significance, or citations, despite high publication and citations in China overall.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the overlay visualization mapping indicated that University of Massachusetts and Kyune Hee University have also made contribution in this field in the recent years (Ayotte et al, 2022;S. M. Kim et al, 2022;Park et al, 2022;Yang et al, 2021). However, the result indicated that no institution in China ranked high regarding publication, significance, or citations, despite high publication and citations in China overall.…”
Section: Discussionmentioning
confidence: 99%
“…Tis is thought to be due to the result that the independence area of nursing was the lowest in the subcategories of nursing professionalism. Tis is because the relationship between doctors and nurses in the medical feld is not a horizontal one, but a hierarchical relationship, which limits the ability of nurses to independently make decisions and fulfll their roles [8,11,16]. However, when nursing professionalism is established, patients can actively exercise their right to self-determination in the decision-making process during treatment by ensuring the patients' right to know and autonomy in the shared decision-making process [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Shared decision-making is based on a shared mental model, which is the perception of, understanding of, or knowledge about a situation or process that is shared among team members through communication [7,8]. Te complexity and criticality of the current healthcare system require shared mental models to enhance safe and efective patient/ client care [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation